TOTAL PHYSICAL RESPONSE: AN EFFECTIVE STRATEGY TO ENHANCE LISTENING COMPREHENSION IN INDONESIAN CLASSROOMS - Hermawan, Heri; Sulkifli (Journal of Language Testing and Assessment, 2025)
This study examines the effectiveness of the Total Physical Response (TPR) method in improving listening comprehension among second-year students at SMPN 1 Libureng-Bone. Addressing the urgent need for more engaging and effective strategies in English language instruction, this research highlights TPR as a movement-based, learner-centered approach. Using a pre-experimental design with a single-group pre-test and post-test, the study involved 30 randomly selected students from Class VIII.D over eight sessions, including treatment. Findings revealed a substantial increase in students’ direct meaning comprehension scores—from a pre-test mean of 4.05 to a post-test mean of 7.9, reflecting a 93% improvement. These results suggest that TPR significantly enhances listening skills by promoting active participation and cognitive engagement. The study contributes to the growing body of research supporting TPR in EFL contexts and offers practical implications for improving English instruction in Indonesian secondary schools.